Begawan Durna Sang Maha Dwijo - Sukatno Sukatno (Institut Seni Indonesia Surakarta, 2022)
Resi Drona or Begawan Durna whose name was Bambang Kumbayana was the son of Resi Baratwaja from the country of Atas Angin or the kingdom of Argajembangan with the goddess Kumbini. Resi Durna, in his youth, had studied with Begawan Ramabargawa. Resi Durna also has a brother named Arya Kumbayana and a sister named Dewi Kumbayani. Resi Durna, who is located in Sokalima hermitage, has a high-spirited and arrogant character. He is a well-spoken person, ingenuity, magic and is good at using heirlooms, besides that, Durna is also good at war tactics. In addition, Durna also has a magic heirloom in the form of a keris named Cundamanik and Sengkali arrows. Because of his supernatural powers and skills in military practice, Resi Durna was appointed and trusted by Begawan Bhisma to become the teacher of the Pandavas and Kauravas.